SPATIAL ANALYSIS OF HIGH CONSERVATION VALUE AREAS AS PROVIDERS OF NATURAL ENVIRONMENTAL SERVICES IN THE KRUENG PEUSANGAN WATERSHED, ACEH PROVINCE - Syafjanuar, Tito Eka; Ichwana Ramli; Nasrul Arahman (Indonesian Journal of Environmental Sustainability, 2024)
Watershed is a unity of ecosystem from upstream to downstream consisting of the main elements of soil, vegetation, water, and air. Watershed has an important function in sustainable community economic development. Changes in land use result in most of the rainwater flowing as surface water which directly or indirectly has caused land degradation. This study aims to identify the presence of high conservation value areas as providers of natural environmental services in the Krueng Peusangan watershed. This study used the HCV Toolkit Indonesia approach and SIG analysis with a tiered quantitative method of slope, soil type, land cover and averaged daily rainfall intensity. The results obtained showed that the Krueng Peusangan watershed has 40.54% of high conservation value areas as providers of natural environmental services, with 23.15% of water supply and flood control areas and 20.01% of erosion and sedimentation control areas. It also identified, 2.67% of the Krueng Peusangan watershed is water supply and flood control areas as well as erosion and sedimentation control areas. This research offers important information about areas providing natural environmental services to the central government, local governments, non-governmental organizations and communities to work together to answer the big challenges in managing the Krueng Peusangan watershed